Central Banking Technical Assistance to Countries in Transition : Papers and Proceedings of the Meeting of Donor and Recipient Central Banks and International Institutions. (International Monetary Fund, 1995)
This book, edited by J.B. Zulu, Ian S. McCarthy, Susana Almuina, and Gabriel Sensenbrenner, presents the proceedings of the special Joint Meetings on Central Banking Technical Assistance held in St. Petersburg, Russia in 1994, and provides detailed information on important issues in central banking, including a comparative sample of 31 countries. The arrangements concerning such issues as the size and composition of the policymaking board, the role of the central bank in monetary and exchange rate policy, resolution of conflict between the central bank and the government, public accountability, relations with the markets, and credit to the government are reviewed.